Estradiol and raloxifene as adjunctive treatment for women with schizophrenia: A meta‐analysis of randomized, double‐blind, placebo‐controlled trials. (27th January 2023) - Li, Zijia; Wang, Yucheng; Wang, Zhe; Kong, Lingtao; Liu, Linzi; Li, Liu; Tang, Yanqing
Abstract: Objectives: We conducted a comprehensive meta‐analysis of all available trials to evaluate the efficacy and safety of estrogen and selective estrogen receptor modulators as adjunctive treatment for women with schizophrenia. Methods: Multiple databases were searched from the inception until March 2022. Only randomized, double‐blind, placebo‐controlled studies (randomized controlled trials) were included. Mean differences (MDs) and their 95% confidence intervals (CIs) were calculated using random effects models. Results: The meta‐analysis included six estradiol versus placebo studies ( n  = 724) and seven raloxifene versus placebo studies ( n  = 419), covering a total of 1143 patients. Adjunctive estradiol outperformed the placebo in terms of the Positive and Negative Syndrome Scale (PANSS) total score (MD = −7.29; 95% CI = −10.67 to −3.91; I 2  = 59.1%; p  < 0.001; k  = 9; N  = 858), positive symptom score (MD = −1.54; 95% CI = −3.04 to −0.72; I 2  = 45.8%; p  < 0.001; k  = 7; N  = 624), negative symptom score (MD = −1.9; 95% CI = −1.77 to −0.34; I 2  = 37.6%; p  < 0.05; k  = 14; N  = 1042), and general psychopathology score (MD = −4.27; 95% CI = −7.14 to −1.41; I 2  = 76.3%; p  < 0.005; k  = 7; N  = 624). Adjunctive raloxifene outperformed the placebo in terms of the PANSS total score (MD = −6.83; 95% CI = −11.69 to −1.97; I 2  = 67.8%; p  = 0.006; k  = 8; N  = 432) and general psychopathology score (MD = −3.82; 95% CI = −6.36 to −1.28; I 2  = 65.3%; p  < 0.005; k  = 8; N  = 432). Conclusions: Our meta‐analysis showed that estradiol and raloxifene are effective and safe adjunctive treatments that improve schizophrenia symptoms in women. Moreover, the effects of estradiol and raloxifene differed in terms of timing and dosage. Both are promising adjunctive treatments that merit further study.